A contribuição do contexto na representação documental de memes - Felix, Luiza Correia Lima (2025)
Memes are defined as replicating units of culture that spread through imitation, transmitting ideas, behaviors, and styles while also evolving and adapting over time. They constitute a communicational object infused with humor and criticism, frequently used as a tool for disseminating ideas, promoting debates, and reflecting on social and political issues. In light of this, the research sought to answer the following question: "What is the contribution of context to the documentary representation of memes?" To address this question, the general objective was established as discussing the role of context in the documentary representation of memes. The following specific objectives were also defined: addressing the documentary aspect of memes; analyzing the informational content in meme messages; examining processes of documentary representation of images; and validating the documentary representation of memes based on the composition of messages and their contexts. To achieve these goals, an exploratory, qualitative, and applied methodological perspective was adopted, involving a bibliographic review and the collection of memes related to the 2022 Brazilian presidential elections, analyzed using the documentary analysis method. For the validation of the proposed protocol, methods based on facet analysis and combinations with theoretical proposals from other authors were used to carry out the documentary representation of memes collected on Instagram. The results demonstrated that memes, as documents, contain multiple contextual layers that should be enriched in their documentary representation, allowing for new perspectives on the cataloging and organization of digital informational documents.